Zero thermal expansion and high Young's modulus in Ti-Nb achieved by concurrent α″iso and ω precipitation. (15th July 2023) - Wang, Haoliang; Lai, Daniel Kuok Zheng; Song, Chenghao; Zhao, Yuliang; Cheng, Jun; Bönisch, Matthias; Sun, Zhenzhong
Abstract: This work develops a novel and efficient processing strategy for creating multi-phase Ti-alloys with zero thermal expansion and enhanced rigidity. By heating to between the start and finish temperatures for martensite reversion, the cold-rolled, α″ martensitic microstructure in Ti22Nb mostly transforms to austenite β, which in turn facilitates the simultaneous precipitation of nano-scale α″iso and ω phases during aging. The diffusional partitioning of Nb leads to the formation of β + α″iso + ω multi-phase microstructures. The crystal-level thermal expansion of α″iso is analogous to athermal α″ martensite, featuring negative thermal expansion along [010]α″ . Macroscopic expansion behavior and Young's modulus are related to the microstructural evolution during aging. Holding at 250 °C increases the initially negative sample-level coefficient of thermal expansion and makes it become zero after aging for 1000 h. A considerable improvement in Young's modulus of 44% could be verified. Graphical abstract: Image, graphical abstract